COMPARISON OF SOME PERSONAL QUALITIES OF STUDENTSSPORTSMEN FROM THE REPRESENTATIVE BASKETBALL AND VOLLEYBALL UNWE TEAMS - S. Stavrev; P. Ivanov (Trakia Journal of Sciences)
One of the main goals of sport activities, apart from improving the technical and tactical skills, general physical state, and etc., is building up and improving of personal qualities. Especially for studentssportsmen, mastering diverse professions, those qualities will not only support their sports career, but contribute to their future professional realization. A number of scientific researches prove the importance of personal qualities in these areas. Volitional qualities and personal anxiety are one of those defined as professionally significant. In this context, we have observed the level of development of the indicated qualities with male sportsmen, being a part of the representative basketball and volleyball UNWE teams and compared them. It would be needed to note that all students-sportsmen have their sports experience of five or more years. When studying the variability of volitional qualities and personal anxiety, the indicators for both studied contingents, are within the limits, defining them as relatively homogeneous. Exceptions are the volleyball players’ volitional qualities, whose results define the group as highly homogeneous. The average values of volitional indicator define students-sportsmen from both teams as personalities with "strong will", who can be relied on. Statistically significant differences when comparing the results were not found in both studied indications.